1977
DOI: 10.1007/bf00345535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light and temperature on leaf anatomy and photosynthesis in Fragaria vesca

Abstract: Fragaria vesca, the woodland strawberry, was grown under a series of controlled environments including variations in light intensity, average temperatures, and temperature amplitude around a constant mean. Observations on CO exchange capacities, leaf anatomy, and cell ultrastructure were made for each treatment to determine relationships between these variables. With increasing light intensity, leaf thickness, leaf density, and mesophyll cell surface area and volume per leaf surface area increased. Net photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
130
2
6

Year Published

1978
1978
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(159 citation statements)
references
References 25 publications
17
130
2
6
Order By: Relevance
“…The shade species, F. moschata and F. nubicola, had significantly higher LDW and LA and lower SLW compared with F. nilgerrensis, a sun-adapted species and F. vesca, which is adapted to a range of habitats. High SLW in the sun-adapted species is consistent with observations of sun-adapted leaves of F. vesca (Chabot and Chabot 1977). This can be attributed to increased mesophyll cell number and size (Chabot and Chabot 1977), increased accumulation of assimilates in the leaf, and high Rubisco content in the leaf as Rubisco can account for 60% of leaf proteins (Schaffer et al 1986).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The shade species, F. moschata and F. nubicola, had significantly higher LDW and LA and lower SLW compared with F. nilgerrensis, a sun-adapted species and F. vesca, which is adapted to a range of habitats. High SLW in the sun-adapted species is consistent with observations of sun-adapted leaves of F. vesca (Chabot and Chabot 1977). This can be attributed to increased mesophyll cell number and size (Chabot and Chabot 1977), increased accumulation of assimilates in the leaf, and high Rubisco content in the leaf as Rubisco can account for 60% of leaf proteins (Schaffer et al 1986).…”
Section: Discussionsupporting
confidence: 77%
“…High SLW in the sun-adapted species is consistent with observations of sun-adapted leaves of F. vesca (Chabot and Chabot 1977). This can be attributed to increased mesophyll cell number and size (Chabot and Chabot 1977), increased accumulation of assimilates in the leaf, and high Rubisco content in the leaf as Rubisco can account for 60% of leaf proteins (Schaffer et al 1986). Poor fruit set has been observed in lower-ploidy species as many have dioecious flowers (Darrow 1966).…”
Section: Discussionsupporting
confidence: 77%
“…Due to their considerable natural physiological diversity, leaves of aquatic plants have been used in many studies of morphological variation. Experiments have demonstrated that a switch from aquatic to aerial placement or a transition from aquatic to terrestrial habitat can result in remarkable changes in leaf physiology and appearance (Chabot and Chabot 1977;Cook 1968;Cook and Johnson 1968). Such differences may indeed be adaptive, improving the fitness of the organism under the new habitat conditions (Schlichting and Pigliucci 1998).…”
Section: Introductionmentioning
confidence: 99%
“…17 The portion of the light that is not used by photosynthesis is converted to heat and raises the temperature of the liquid in and around the cell leading to water evaporation. 18 The water vapor finds an outlet to the outside through openings in the leaf membrane. These openings are called stomata.…”
mentioning
confidence: 99%